2019
DOI: 10.1136/bmjnph-2018-000018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of salt-related knowledge, attitudes and behaviours between parents and caregivers of children under 18 years of age and other adults who do not care for children under 18 years of age in Victoria, Australia

Abstract: Background/AimsSalt intake among Australian adults exceeds recommendations, increasing the risk of cardiovascular disease. Knowledge, attitudes and behaviours (KABs) are modifiable factors that may influence salt consumption. It is not known whether salt-related KABs among parents and caregivers of children under 18 years of age differ from other adults who do not care for children under 18 years of age. Therefore, we aimed to determine whether salt-related KABs differed between parents and caregivers and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The findings of the study indicated that only 47% of the respondents are of the view that what they eat and drink are healthy and find no reason to make changes. This was in line with an Australian study done by Khokhar et al ( 2019 ), which reported that the majority of caregivers were concerned about the amount of fat, sugar and salt added to their meals and perceived that reducing the amount of salt, fats and sugar in their meals will lead to better health. In a study by Sharma et al ( 2018 ), caregivers reported that they preferred unhealthy junk foods such as snacks and beverages because of being convenient as compared to healthy foods that take time to prepare.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the study indicated that only 47% of the respondents are of the view that what they eat and drink are healthy and find no reason to make changes. This was in line with an Australian study done by Khokhar et al ( 2019 ), which reported that the majority of caregivers were concerned about the amount of fat, sugar and salt added to their meals and perceived that reducing the amount of salt, fats and sugar in their meals will lead to better health. In a study by Sharma et al ( 2018 ), caregivers reported that they preferred unhealthy junk foods such as snacks and beverages because of being convenient as compared to healthy foods that take time to prepare.…”
Section: Discussionsupporting
confidence: 90%
“…Given the knowledge of the current excessive sodium intake in Spanish children and the benefits of decreasing salt intake from an early age to reduce the likelihood of a diet high in salt during adulthood or to prevent cardiovascular disease [16], it is useful to try to understand current patterns involving schoolchildren and their environment regarding behaviors related to salt intake. These behaviors include the use of discretionary salt (adding salt at the table or when cooking) and checking the sodium content on food labeling [17]. Furthermore, given children’s vulnerability to developing a preference for salty foods, it would be interesting to analyze whether these behaviors are related to children’s greater preference for salty foods.…”
Section: Introductionmentioning
confidence: 99%